Mast Cell Sarcoma of the Retroperitoneum With Concurrent Systemic Mastocytosis and an Undisclosed Associated Hematologic Neoplasm: A Case Report - Ing Chen; Jia-Bin Liao; Jung-Chia Lin; Pin-Pen Hsieh; Ming-Yun Hsieh (SAGE Publishing, 2022)
Mastocytosis is a rare disorder affecting both children and adults by gathering of functionally defective mast cells in the body's tissues. The World Health Organization (WHO) classified mastocytosis into cutaneous mastocytosis, systemic mastocytosis (SM), and mast cell sarcoma (MCS). We hereby present a case of retroperitoneal MCS with concurrent systemic mastocytosis and an undisclosed associated hematological neoplasm (SM-undisclosed AHN). The diagnosis of MCS and SM was made after the second biopsy over retroperitoneal mass, lymph node, and ovary for rapidly progressive disease with the presentation of unexplained recurrent flushing, palpitation, and shock, in addition to abdominal pain. A clonal myeloid neoplasm was also suspected by the karyotype and hemogram data. Unfortunately, the patient succumbed to the disease quickly. Apart from this unique case, the previously reported cases of SM with MCS in the literature were also reviewed.